CASE REPORT Sapho – a case report - Maślińska, Maria (Reumatologia/Rheumatology, 2005)
The case of the 36-year old female patient with osteosclerotic and osteolotic osteoarticular changes and hyperostosis of the spine is presented. She had suffered from spinal pain for ten years and she had clavicular pain. The changes were localized in particular in the anterior chest wall and sacroiliac joints. Mainly clinical features and results of the radiography, MRI and scinthigraphy enabled diagnosis of SAPHO syndrome. The diagnosis of the SAPHO syndrome is made difficult by its unknown cause, long and covert progress. The correlation with the pathological skin changes may be only transient or does not take place at all. The syndrome has to be differentiated from Paget disease, Ewing sarcoma, myeloma multiplex and bacterial inflammation of bone and marrow. In the presented case the diagnosis was eventually made ten years after when the first complaints of pain and bone deformations were noted.